Simulation as Part of Discharge Teaching for Parents of Infants in the Neonatal Intensive Care Unit. Issue 2 (March 2017) - Raines, Deborah A.
Abstract: Background: Simulation has become accepted as a method to increase confidence among healthcare professionals. We felt simulation might have similar benefits for parents of babies about to be discharged from the neonatal intensive care unit. Purpose: We developed the Neonatal Home Environment Learning Program to promote parental confidence in anticipation of their infant's discharge from the neonatal intensive care unit. Methods: This evaluation study was conducted with 15 mother/father dyads. Each participant recorded a self-perceived confidence score before and after the simulation experience. Participants also completed a program evaluation and participated in a debriefing session. Confidence scores (pre- and postsimulation) and evaluation scores were analyzed with descriptive statistics. Responses from the debriefing sessions were analyzed using descriptive phenomenology. Results: Parents rated the simulation experience highly. During debriefings, parents shared that the simulation made them feel more prepared. Two themes emerged from the debriefing data: doing it alone was different than I expected and feeling more confident. Clinical Implications: A simulation experience for parents helps to ensure a positive transition to home and safe, effective care after discharge of the infant. Abstract : Parents watching the nurse caring for their baby, followed by return demonstrations are traditional methods of discharge teaching for parents of babies in the neonatal intensive care unit (NICU). Simulation is widely used for enhancing learning of healthcare professionals, but little is known about simulation for family caregivers such as parents of a baby being discharged from the NICU. A program involving simulation as part of NICU parents' discharge teaching is presented.